(untitled) (Research, Society and Development, 2022)
Until recently, taste and appearance were the most important attributes of fresh fruits and other vegetables, but nowadays, consumers are more concerned about food safety and nutritional values, demanding to use less chemicals in fruits and vegetables. In this context, much attention has been given to the search for natural substances capable of acting as antimicrobials and antioxidants, being an alternative to the products used in the maintenance of food quality. This increased interest has intensified due to concerns about the limited natural resources of the fossil fuel reserve and the environmental impact caused by the use of non-biodegradable plastic-based packaging materials. The demand for renewable and biodegradable products has become an important strategy in the effort to reduce the polluting impact of packaging on the environment. To overcome this problem, an edible coating approach can be used where biopolymers emerge as possible replacements for petroleum-based packaging materials. Known as “green plastics” or bioplastics, they are made from biodegradable polymers such as starches, cellulose, and sodium alginate, among others, with numerous studies being conducted to investigate the ability of edible toppings to preserve the quality and extend the shelf life of fresh fruits and vegetables. This is possible due to their acting by regulating the metabolic activities of the fruits and the addition of active ingredients that interact with the product.